Molecular identification and high fidelity micropropagation of shell ginger (Alpinia zerumbet) - Shashanka Shekhar Sarker; Kh. Muhim Ahmed; Tanzena Tanny; Shamima Nasrin; A. H. M. Mahbubur Rahman; Keshob Chandra Das; Iftekhar Alam (All Life, 2023)
Alpinia zerumbet is a medicinal and ornamental plant of the Zingiberaceae family cultivated in many parts of the world. The plant is medicinally important and often misidentified with closely related species. The objective of this work was to establish its DNA-based identity and a protocol for high-fidelity micropropagation to support the medicinal plant industry. PCR amplification and subsequent sequencing of RuBisCO large subunit (rbcL) and Maturase K (matK) gene successfully report its DNA barcode. In vitro shoots were induced the best from rhizome buds on Murashige and Skoog (MS) medium supplemented with 6.0 mg L−1 6-benzyl amino purine and 30 g L−1 sucrose. Microshoots were rooted well in MS medium amended with 1.5 mg L−1 naphthalene acetic acid. Plantlets were satisfactorily acclimated to soils maintained in a growth chamber and subsequently in the open air for 10–20 days. Analyzing eight random amplified polymorphic DNA and eight inter-simple sequence repeat primers resulted in 53 and 60 distinct bands, respectively. Uniform banding patterns suggest the genetic uniformity of the micropropagated plants. The results offer an accurate identification of A. zerumbet from any plant tissue. The micropropagation protocol would be helpful for economically feasible and environmentally sustainable exploitation of this valuable plant.